Optimizing the Principles of Healthy Business Competition and the Role of KPPU for a Fair Economy in the Digital Era - Sudiruddin; Wibowo, Agung Satryo; Darmawan, Didit; Halizah, Siti Nur; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2023)
Technological developments have assisted businesses in developing their businesses actor. The application of the principle of fair business competition in Indonesia, in accordance with Article 33 of the 1945 Constitution, plays an important role in improving public welfare and promoting the country’s economic development. Through Law Number 5 Year 1999, this regulation prohibits monopolistic practices and abuse of dominant position, creating a fair and transparent business environment. The Business Competition Supervisory Commission (KPPU) has a crucial role in enforcing this regulation by conducting supervision, investigation, and enforcement of violations. KPPU is also focusing on the digital sector, where new challenges arise due to the dominance of large companies. By increasing transparency, education, and collaboration with international institutions, it is hoped that Indonesia can create a healthier and more sustainable business ecosystem, which in turn will improve community’s quality of life and overall economic growth. Legal protection for business actors is anticipatory, prohibiting acts of unfair competition, and imposing sanctions. Repressive protection occurs if there is a violation of Law Number 5 Year 1999. Competition in the digital market is increasingly complex, with access to consumer data control and the increasing market power of digital platforms. KPPU is expected to play a role in supervision and law enforcement in the digital economy in accordance with statutory regulations.